2001
DOI: 10.1200/jco.2001.19.16.3685
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Graft-Versus-Host Disease After Allogeneic Peripheral-Blood Stem-Cell and Bone Marrow Transplantation: A Meta-Analysis

Abstract: Both acute and chronic GVHD are more common after PBSCT than BMT, and this may be associated with lower rates of malignant relapse. The magnitude of the transfused T-cell load may explain the differences in chronic GVHD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
234
7
10

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 392 publications
(265 citation statements)
references
References 30 publications
14
234
7
10
Order By: Relevance
“…Several reports have shown that the use of peripheral blood as a source of haematopoietic stem cells increased the incidence of chronic GVHD (Cutler et al, 2001;Przepiorka et al, 2001;Flowers et al, 2002). However, stem cell source did not influence GSS or the duration of systemic IST in our study.…”
Section: Discussioncontrasting
confidence: 71%
“…Several reports have shown that the use of peripheral blood as a source of haematopoietic stem cells increased the incidence of chronic GVHD (Cutler et al, 2001;Przepiorka et al, 2001;Flowers et al, 2002). However, stem cell source did not influence GSS or the duration of systemic IST in our study.…”
Section: Discussioncontrasting
confidence: 71%
“…The incidence of chronic GvHD was higher than that in our previous experience (56%) [32] or in other reports [31,33] even after considering inevitable differences in the ethnicity, GvHD prophylaxis and matching practice of HLA, or disease risk. G-CSF mobilized peripheral blood stem cells may have been associated with an increased incidence of GvHD, particularly in its chronic form [34,35]. Conditioning regimen excluded antithymocyte globulin was also a possible explanation of this finding [23].…”
Section: Discussionmentioning
confidence: 96%
“…[20][21][22] However, administration of rhG-CSF leads to high serum levels in individuals, exceeding endogenous G-CSF levels measured under physiological and pathophysiological conditions, leading to adverse events in a number of them. 7 In contrast to BM, which is collected under general anesthesia by multiple aspirates from the iliac crest, a good peripheral venous access is a requirement for successful PBPC collection.…”
Section: Discussionmentioning
confidence: 99%